RASCH MODEL ANALYSIS ON MATHEMATICS TEST INSTRUMENTS: BIBLIOSHINY (1983-2023) - Nofriyandi; Zafrullah; Sa'adatul Ulwiyah (Mathematics Research and Education Journal, 2023)
The Rasch Model is a very useful tool in testing the quality of a measurement instrument, including mathematics tests. The Rasch model is part of item response theory which can classify item and person calculations in one distribution map. This research analyzes research trends regarding Rasch models in mathematics instruments, using bibliometric analysis to understand the current state of research in this field. From the analysis obtained, it can be said that publications regarding Rasch models in mathematical instruments have increased rapidly from 1983 to 2023, with a total of 173 articles. Universiti Kebangsaan Malaysia holds the highest affiliation with 13 articles. The Journal of Applied Measurement is the most prolific publication with 10 articles and 113 citations. Printy (2008) and Clements et al., (2008) are the sources with the most total citations, namely 139 citations. Azrilah Abdul Aziz, Clelia Cascella, Chiara GIBERTI, and Azami Zaharim are the authors with the largest number of articles discussing Rasch models in mathematical instruments with 4 articles. New themes that emerge in this analysis are mathematics education, engineering education, validity, reliability, gender, and differential item functioning so that future researchers can consider the keywords above